Peter Paul Rubens and the Counter-Reformation crisis of the beati moderni - Noyes, Ruth S. (Sanctity in Global Perspective, 2018)
chapter Introduction: bitter pills -- chapter 1 Among the others -- chapter 2 Keep a close eye -- chapter 3 Incredible costs -- chapter 4 Has not pleased -- chapter 5 “Give it to me”.